Sustaining multilateralism, cross-cultural learning and domestic cooperative internationalism - Mensah, Chaldeans (My University, 2017)
This paper reports on the NMUN Japan experience from a North American perspective by examining the dynamics of experiential learning, cross-cultural interactions among delegates and with the local culture, an how the conference used widespread media coverage in an effort to build new constituencies in Japan for multilateralism and cooperative internationalism, defined as “an orientation toward international affairs that stresses concern for others abroad with whom one should work toward common goals.”
Keywords: model United Nations simulations; peace studies; negotiation; experiential learning; cross-cultural interactions